Assessing the attractiveness of cryptocurrencies in relation to traditional investments in South Africa - Letho, Lehlohonolo (Graduate School of Business (GSB), 2019)
The dissertation examined the effect of cryptocurrencies on the portfolio risk-adjusted returns of traditional and alternative investments using daily arithmetic returns from August 2015 to October 2018 of traditional assets (South African stocks, bonds, currencies), alternative assets (commodities, South African real estate) and cryptocurrencies (Cryptocurrency index (CRIX) and ten other individual cryptocurrencies). This is worth investigating as cryptocurrencies have been performing well while the listed equities in South Africa and most alternative investments have been underperforming (Srilakshmi & Karpagam, 2017). The mean-variance analysis, the Sharpe ratio, the conditional value-at-risk (CVaR) and the mean-variance spanning techniques were employed to analyse the data. The spanning test carried out was the multivariate ordinary least squares (OLS) regression Wald test. The research findings showed that the inclusion of cryptocurrencies in a portfolio of investments improves the efficient frontier of the portfolio of investments and the portfolio of investments risk-adjusted returns. Moreover, the findings suggested that cryptocurrencies are good portfolio diversification assets. However, investments in cryptocurrencies should be made with caution as the risks of investments are high in relation to traditional and alternative investments. The findings of this study advocate for individual and institutional investors to include cryptocurrencies within their South African portfolio of traditional and alternative investments.